Supervised Physical Training Enhances Muscle Strength but Not Muscle Mass in Prostate Cancer Patients Undergoing Androgen Deprivation Therapy: A Systematic Review and Meta-Analysis - Chen, Ziyuan; Zhang, Yuan; Lu, Chunyan; Zeng, Hao; Schumann, Moritz; Cheng, Sulin (Frontiers in Physiology, 2019)
Introduction: Androgen deprivation therapy (ADT) is considered the basic treatment for advanced prostate cancer, but it is highly associated with detrimental changes in muscle mass and muscle strength. The aim of this meta-analysis was to investigate the effects of supervised physical training on lean mass and muscle strength in prostate cancer patients undergoing ADT. Methods: A systematic literature search was performed using MEDLINE, Embase, and ScienceDirect until October 2018. Only studies that examined both muscle mass and strength in prostate cancer patients undergoing ADT were included. Outcomes of interest were changes in lean body mass (surrogate for muscle mass) as well as upper and lower body muscle strength. The meta-analysis was performed with fixed-effects models to calculate mean differences between intervention and no-training control groups. Results: We identified 8,521 publications through the search of the following key words: prostate cancer, prostate tumor, prostate carcinoma, prostate neoplasm, exercise, and training. Out of these studies, seven randomized controlled trials met the inclusion criteria and where included in the analysis. No significant mean differences for changes in lean mass were observed between the intervention and control groups (0.49 kg, 95% CI: −0.76, 1.74; P = 0.44). In contrast, the mean difference for muscle strength was significant both in chest (3.15 kg, 95% CI: 2.46, 3.83; P < 0.001) and in leg press (27.46 kg, 95% CI: 15.05, 39.87; p < 0.001). Conclusion: This meta-analysis provides evidence that low- to moderate-intensity resistance and aerobic training is effective for increasing muscle strength but may not be sufficient to affect muscle mass in prostate cancer patients undergoing ADT. The underlying mechanisms for this maladaptation may in part be explained by an insufficient stimulus induced by the training regimens as well as a delayed initiation of training in relation to the start of ADT. When interpreting the present findings, one should bear in mind that the overall number of studies included in this review was rather low, emphasizing the need for further studies in this field.